Between a Rock and a Hard Place: The Challenges of Caregiving During a Pandemic for Parkinson's Family Care Partners. (July 2023) - Seshadri, Sandhya; Norton, Sally A.; Stahl, Tyler; Shah, Mina; Dini, Megan; Yarab, Nicole; Holtrop, Jodi Summers; Kluger, Benzi M.
Aim : To understand Parkinson's Disease (PD) care partners' a) specific challenges that led to worsening strain and b) their suggestions for supports to help them during the ongoing pandemic.Method : Using a qualitative descriptive design, semi-structured interviews with family care partners (n = 19) were completed. Participants were recruited from 10 sites across the United States that varied in size, demographics of patient population served, and geographic location (urban, suburban, rural). Interviews were audio-recorded, de-identified, transcribed verbatim, and coded in a phased manner. The research team analyzed the data and identified themes.Results : During the pandemic, the already difficult task of caregiving was made worse by having to choose between poor options. Five themes exemplified PD care partner experiences: (1) Managing risks and benefits of medical care in settings outside the home vs meeting these needs at home; (2) Struggling to maintain employment benefits with the costs of care and risks of bringing in outside caregivers; (3) Struggling to balance caregiving and self-care; (4) Struggling to be supportive and taking on new caregiving roles in the face of less support services; and (5) Wanting social connections and feeling pressured to maintain isolation. Care partners wanted timely access to, and guidance from healthcare teams to help them.Conclusions : Care partner burden was worsened by lack of guidance when confronted by choices that could lead to negative outcomes. Movement disorder and palliative care providers may be able to alleviate some care partner burden through building systems for timely access and guidance.